Diastereoselective C-alkylation of aldimines, derived from chiral alpha-carbon heteroatom substituted aldehydes, with triethylborane. Application to the synthesis of benzylisoquinolines - Fuentes-Ríos, David; Muñoz, Carmen; Díaz-Morilla, Amelia; Sarabia-García, Francisco Ramón; López-Romero, Juan Manuel (Royal Society of Chemistry, 2023)
The one-pot reaction of a chiral aldehyde, p-methoxyaniline or p-fluoroaniline, and triethylborane produces the corresponding alkylated chiral amine with high yields and distereoisomeric ratios. Stereocontrol is induced by the presence of a heteroatom in the alfa-position to the aldehyde. In case of alkylation of imines derived from chiral aliphatic amines, good yields and moderate to high diastereoselectivity are obtained: yields are significantly better when the preformed imine is used in the reaction with triethyl borane, and diastereoselectivity of the reactions is largely depending on the structure of the chiral aliphatic amine. The methodology is successfully applied to the synthesis of romneine, a natural benzylisoquinoline.
Keywords: Aminas; Benzylisoquinolines; Aldimines; Diastereoselectivity; Triethylborane